基于Visual Lisp机械零件图形尺寸参数化标注设计 - 苏艳萍; 王鸿钧 (Jixie chuandong)
Based on Visual Lisp in the AutoCAD,dialog box type mark system of size tolerance,shape and position tolerance and roughness is developed,automatic mark of the tolerance and roughness is realized.A kind of simple mark method of the tolerance and roughness is provided.